Chilean Virtual Observatory and Integration with Alma - Parada-Daza, V (SPIE, 2014)
The Virtual Observatories strive to interoperate, exchange data and share services as if it was only one big VO. In this work, the state of the art of VOs will be presented and summarized in a schematic diagram with the frequency range of the observed data that every VO publishes. Chile, currently a member of the IVOA, collaborates with the Atacama Large Millimeter/submillimeter Array (ALMA), to study and propose ways to adequate the data generated by ALMA to the different data model proposed by the IVOA. © 2014 SPIE.